Clinically relevant correction of recessive dystrophic epidermolysis bullosa by dual sgRNA CRISPR/Cas9-mediated gene editing - Bonafont, Jose; Haußer-Siller, Ingrid (Molecular therapy, 2019)
Gene editing constitutes a novel approach for precisely correcting disease-causing gene mutations. Frameshift mutations in COL7A1 causing recessive dystrophic epidermolysis bullosa are amenable to open reading frame restoration by non-homologous end joining repair-based approaches. Efficient targeted deletion of faulty COL7A1 exons in polyclonal patient keratinocytes would enable the translation of this therapeutic strategy to the clinic. In this study, using a dual single-guide RNA (sgRNA)-guided Cas9 nuclease delivered as a ribonucleoprotein complex through electroporation, we have achieved very efficient targeted deletion of COL7A1 exon 80 in recessive dystrophic epidermolysis bullosa (RDEB) patient keratinocytes carrying a highly prevalent frameshift mutation. This ex vivo non-viral approach rendered a large proportion of corrected cells producing a functional collagen VII variant. The effective targeting of the epidermal stem cell population enabled long-term regeneration of a properly adhesive skin upon grafting onto immunodeficient mice. A safety assessment by next-generation sequencing (NGS) analysis of potential off-target sites did not reveal any unintended nuclease activity. Our strategy could potentially be extended to a large number of COL7A1 mutation-bearing exons within the long collagenous domain of this gene, opening the way to precision medicine for RDEB.